The Anglo-Japanese Alliance (Nichi-Ei Dōmei) as confirmation of the zones of influence of the British Empire and Japan in Southeast Asia in the early twentieth century - Plesiewicz-Świerczyńska, Izabela (The British Empire: Interdisciplinary Deliberations, 2019)
The first Anglo-Japanese Alliance was signed in London, on 30 January 1902, by Lord Lansdowne (British foreign secretary) and Hayashi Tadasu (Japanese minister in London). The alliance bound Britain and Japan to assist one another in safeguarding their respective interests in China and Korea. It was a diplomatic milestone that saw an end to Britain’s splendid isolation. Directed against Russian expansionism in the Far East, it was a cornerstone of British and Japanese policy in Asia until after World War I. The alliance was renewed and expanded in scope twice, in 1905 and 1911. It was specifically terminated by the Four-Power Pacific Treaty (1921).